The judicial review of the substance of constitutional amendments in comparative constitutional law - Chilo Gutiérrez, Evelyn Milagros (2021)
This paper addresses a particular scenario of the classic tension between constitutionalism and democracy, one that poses the existence of material limits to the power of constitutional reform. The subject undoubtedly raises a series of perplexities around some aspects such as the legal nature of the constitutional reform power. The essay analizes the defense of implicit material limits when the constitutional text has not explicitly recognized them, the competence and legitimacy of the courts, the normative parameter in merit to which this control would be carried out, among others. In this context, this article proposes to provide an analysis of these issues based on comparative law, exposing the cases of Germany, the United States and Colombia, countries that have provided different answers to the issue of material limits in function of their own constitutional texts and systems, and whose arguments are relevant to constitutional theory.